Automatic Meter Reading System Based on Wireless Mesh Networks and SOPC Technology - Liting Cao; Wei Jiang; Zhaoli Zhang (2009 Second International Conference on Intelligent Networks and Intelligent Systems, 2009)
AMR system is a system used to automatic reading the measure meters of energy consumption. A remote wireless AMR system based on wireless mesh networks and SOPC technology is presented in this paper to solve the problems in existing AMR system. The system consists of measure meters, wireless sensor nodes, data collector, management centre and wireless communication networks. The data transmit from the sensor nodes to the data collector using ZigBee communication network. The system uses Ethernet transmit data from the data collector to the management centre. The data collector act as gateway, we adopt wireless mesh network topology structures. Management center is designed based on FPGA EP2C35F672C8. In ZigBee sensor node design, MEGA128 was adopted as processor. Wireless chip CC2420 is adopted in communication unit. Simulation results show that the method proposed in this paper is possible to implement practical application in the remote AMR system. The system presented in this paper have many significant excellences, such as networked, wireless, moveable, high-veracity and lower power-consuming. The using of SOPC technology improves the agility of system, the IP core can be rebuilt according to the real needs of system very expediently. The proposed system have abroad application foreground in the real application field to remote measure and manage of electric power, water supply, gas supply and heat supply.